Coupling effect of nanoscale zero-valent iron and sodium lauroyl sarcosinate on the biogas biological upgrading from kitchen wastewater by anaerobic digestion. Issue 1 (February 2023) - Zhao, Mingxing; Tang, Jieyu; Liu, Ziyi; Miao, Hengfeng; Shi, Wansheng; Huang, Zhenxing; Ruan, Wenquan
Abstract: In this study, nanoscale zero-valent iron (nZVI, 6 g/L) and sodium lauroyl sarcosinate (SLS, 0, 10, 30, 50 and 70 mg/L) were used to promote anaerobic digestion of kitchen wastewater for methane (CH4 ) generation. The maximum CH4 content, yield and BMP were 96.23%, 250 mL/gVS and 82.46% at SLS dosage of 30 mg/L, respectively; addition of > 50 mg/L SLS resulted in prolonging lag phase time of methane production due to the degradation intermediate lauric acid (LA). In addition, SLS reduced the surface tension of liquid by forming molecular film at the interface, promoting the continuous gas-liquid contact and improving the mass transfer efficiency of hydrogen (H2 ). The pH values in the two systems remained in the range of 7.54–7.62 and 7.20–7.30, respectively. Enzyme activity assays showed that nZVI/SLS co-addition increased the activities of dehydrogenase (by 13.26∼34.36%) and coenzyme F420 (by 35.37∼82.93%), compared to control. The co-addition of nZVI/SLS could increase extracellular polymeric substances (EPS) production by anaerobic microorganisms; compared with the control, the ratio of protein/polysaccharide increased, indicating that the microbial flocculation ability was promoted. Microbial community structure showed that the relative abundance of Methanomicrobiales and Methanolinea visibly increased from 6.88% and 3.08–17.56%∼30.22% and 5.18∼7.67%, respectively, after the SLS addition. Graphical Abstract: ga1 Highlights: Nanoscale zero-valent iron and sodium lauroyl sarcosinate promoted CH4 generation. Sodium lauroyl sarcosinate promoted hydrogen release by nanoscale zero-valent iron. 30 mg/L sodium lauroyl sarcosinate led to the highest methane content of 96.23%. Hydrogenotrophic methanogens were enriched after anaerobic digestion.